Características de la madera de Cedrela odorata L. (cedro amargo, Meliaceae) en Costa Rica. - Arnáez, Elizabeth; Flores, Eugine (Revista de Biología Tropical, 1988)
Cedrela odorata L. is a deciduous tree 30-35 m height and 1.5 m in diameter, native to Costa Rica, which grows in areas ranging from 1500-3000 m.s.n.m. The wood has coarse and heterogeneous texture, linear grain and superposed areas in tangential section with 2-4 growth rings 12.5 cm. Porosity is diffuse, circular or semicircular. There is variation in pore size, vessel element length, fiber length, cell wall thickness of fibers and ray composition between specimens collected at different localities. Runkel factor corresponds to Group IV, regular for pulp production; however, the physical and mechanical characteristics show the wood to be excellent for building and cabinetwork.